Relationship between lower lumbar spine shape and patient bone metabolic activity as characterised by 18F NaF bio-markers. (January 2020) - Yeung, S.; Toor, A.; Deib, G.; Zhang, J.; Besier, T.; Fernandez, J.
Abstract: Chronic lower lumbar pain has been associated with elevated bone metabolic activity in the spine. Diagnosis of bone metabolic activity is currently through integrating Positron Emission Tomography (PET) with Sodium Fluoride ( 18 F–NaF) biomarkers. It has been reported that numerous observable pathologies including lumbar fusion, disc abnormalities and scoliosis have often been associated with increased 18 F–NaF uptake. The aim of this study was to identify what features of lower lumbar shape most strongly correlate with 18 F–NaF uptake. Following a principal component analysis of 23 patients who presented with lumbar pain and underwent 18 F–NaF PET-CT, it was revealed that three modes interpreted as (i) sacral tilt, (ii) vertebral disc spacing and (iii) spine size were the three characteristics that described 88.7% of spine shape in our study population. 18 F–NaF was described by two modes including 18 F–NaF intensity and spatial variation (anterior-inferior to posterior-superior). 18 F–NaF was most sensitive to sacral tilt followed by vertebral disc spacing. A predictive model derived from that spine population was able to predict 18 F–NaF 'hot-spot' locations with 85 ± 5% accuracy and with 71 ± 3% accuracy for the 18 F–NaF magnitude. These results suggest that patients reporting with lower lumbar pain and who present with increased sacral tilt profiles and/or reduced disc spacing are good candidates for further 18 F–NaF PET-CT imaging, evidenced by the high association between those shape profiles and 18 F–NaF uptake. Highlights: Sacral tilt, vertebral disc spacing and spine size represent 88.7% of spine shape. Our PLSR model can predict 18 F–NaF spine 'hot-spots' with 85 ± 5% accuracy. 18 F–NaF was most sensitive to sacral tilt followed by vertebral disc spacing. Patients who present these profiles are good candidates for 18 F–NaF PET-CT.